FENOMENA POLITIK UANG (MONEY POLITIC) PADA PEMILU TAHUN 2019 DI KABUPATEN CIAMIS - Fahmi Fajar Mustopa; Sarip Sarip (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The phenomenon of money politics that occurs in the community is very difficult to stop and it has become a habit that certain political candidates or contestants do to the public ahead of the election to gain support and gain the most votes from the community without considering the quality of the political candidates or contestants they choose. This study was conducted to determine the factors that cause money politics, how the process occurs, the impact of money politics and suggestions to overcome the occurrence of money politics. This research uses descriptive qualitative method by analyzing the paradigm of social behavior. The research location is in Ciamis Regency. Sources of information in this study consisted of the community, the success team of political candidates or contestants and other important figures. The results of the study show that (1) the factors that influence the occurrence of money politics are the poverty factor, the habit factor, and the community knowledge factor. (2) The process of the occurrence of money politics is carried out directly with the term dawn attack or by mobilizing the masses in the form of money directly or in other goods such as building facilities for prayer rooms, roads and others. (3) The impact arising from the practice of money politics can damage the democratic order and can cause other new problems in society to the government, so that it has a long-term negative impact. (4) Suggestions to anticipate the occurrence of money politics, there must be strategic steps taken by the government and all parties for the realization of good democracy in the future, namely, political education for the community must be increased, punishment must have a deterrent effect for money politics actors, and need regulatory changes. Keyword: Political Money, Elections, Legislative, Districts Ciamis